Nanosized food additives impact beneficial and pathogenic bacteria in the human gut: a simulated gastrointestinal study. (December 2018) - Siemer, Svenja; Hahlbrock, Angelina; Vallet, Cecilia; McClements, David; Balszuweit, Jan; Voskuhl, Jens; Docter, Dominic; Wessler, Silja; Knauer, Shirley; Westmeier, Dana; Stauber, Roland
Abstract Nanotechnology provides the food industry with new ways to modulate various aspects of food. Hence, engineered nanoparticles (NPs) are increasingly added to food and beverage products as functional ingredients. However, the impact of engineered as well as naturally occurring NPs on both commensal and pathogenic microorganisms within the gastrointestinal tract (GI) is not fully understood. Here, well-defined synthetic NPs and bacterial models were used to probe nanoparticle–bacteria interactions, from analytical to in situ to in vitro. NP–bacteria complexation occurred most efficiently for small NPs, independent of their core material or surface charge, but could be reduced by NPs' steric surface modifications. Adsorption to bacteria could also be demonstrated for naturally occurring carbon NPs isolated from beer. Complex formation affected the (patho)biological behavior of both the NPs and bacteria, including their cellular uptake into epithelial cells and phagocytes, pathogenic signaling pathways, and NP-induced cell toxicity. NP–bacteria complex formation was concentration-dependently reduced when the NPs became coated with biomolecule coronas with sequential simulation of first oral uptake and then the GI. However, efficient NP adsorption was restored when the pH was sufficiently low, such as in simulating the conditions of the stomach. Collectively, NP binding to enteric bacteria may impact their (patho)biology, particularly in the stomach. Nanosized-food additives as well as naturally occurring NPs may be exploited to (rationally) shape the microbiome. The information contained in this article should facilitate a "safe by design" strategy for the development and application of engineered NPs as functional foods ingredients. Nanotechnology: how nanoparticles impact the gut microbiome Engineered or naturally occurring nanoparticles could potentially affect the bacteria in the gut. A study led by Dana Westmeier and Roland Stauber from University Medical Center of Mainz, Germany probed the nanoparticle–bacteria interactions in situ. They found that NP–bacteria complex occurred most efficiently for small NPs, independent of their core material or surface charge. The complex formation affected the (patho)biological behavior of both the NPs and bacteria, particularly under conditions that simulate the stomach. The result shows that both engineered and naturally occurring nanoparticles could be exploited to shape the gut microbiome. The study can offer guidelines for future development and application of nanoparticles in food industry.